Modelling the pathophysiology of schizophrenia and methamphetamine-induced psychosis: A structural magnetic resonance imaging and cytokine study - Blake, Lauren (Department of Psychiatry and Mental Health, 2023)
Background: There is overlap in the symptomatology and psychobiology of schizophrenia (SCZ) and methamphetamine-induced psychosis (MAP). In schizophrenia there are reports of significant associations of increased severity of psychotic symptoms with thinner frontal cortex and decreased hippocampus and amygdala volume, and there is evidence of increased TNF-α and interleukin (IL)-1β concentrations compared to healthy controls. However, no studies to date have 1) compared structural findings in SCZ and MAP, 2) investigated the associations of psychotic symptom severity and duration with brain volumes and cytokine concentrations in SCZ and MAP and 3) determined the effect of antipsychotic type on brain measures in SCZ compared to MAP. Methods: 36 patients with SCZ, 27 with MAP, and 32 healthy controls underwent clinical interview, structural magnetic resonance imaging (MRI) and phlebotomy. Symptom severity was assessed with the positive and negative symptom scales (PANSS). Volumes of the amygdala, hippocampus and basal ganglia and frontal cortical thickness and surface area were processed with FreeSurfer. TNF-α, IL-1β, -8, -12 and IFN-γ concentrations in serum, were assessed with a Luminex assay. ANOVAs were used to compare structural findings across groups, group differences for cytokine concentrations, number of psychotic episodes, symptom severity and to determine the effect of antipsychotics (AP) type on structural brain volumes and frontal cortical thickness in SCZ and MAP. Spearman's Rank and Pearson's correlations were used to determine associations of symptom severity, number of psychotic episodes and duration of illness with structural brain measures and cytokine concentrations. Results: 1) Decreased left amygdala volumes were reported in SCZ and MAP compared to CON, 2) increased right caudate and bilateral putamen and NAcc (nucleus accumbens) volumes were reported in SCZ compared to MAP and CON , with increased right pallidus volumes in SCZ compared to MAP, 3) decreased frontal cortical thickness was reported in SCZ and MAP compared to CON, 4) decreased frontal cortical surface area of the right pars opercularis and left pars triangularis was reported in SCZ compared to CON, 5) duration of illness was negatively correlated to decreased left amygdala volumes and frontal cortical thickness and surface area in SCZ, 6) there was a significant association between longer MA duration of use with decreased hippocampal and amygdala volumes and decreased frontal cortical thickness and surface areas in MAP, 7) significant effects of AP type were reported for frontal cortical thickness, 8) cytokine concentrations did not differ significantly between CON, SCZ and MAP and 9) number of psychotic episodes were greater in SCZ compared to MAP. Conclusions: These findings are consistent with the presence of both overlaps (e.g., in amygdala volume and frontal cortical thickness) and differences (e.g., in basal ganglia volume,) in the neurobiology of SCZ and MAP. It is noteworthy that longer illness duration is associated with decreased left amygdala volumes and frontal cortical thickness in SCZ and not MAP, suggesting that illness duration does not impart gray matter volume decreases in MAP. In MAP, MA use duration has significant associations with decreased left amygdala volumes, frontal cortical thickness and surface area in MAP. Decreased left amygdala volumes and frontal cortical thickness in both disorders suggest neurobiological overlap across these conditions, which may signify clinical importance in treatment of these conditions. Future studies involving magnetic resonance spectroscopy and imaging on the brain regions investigated in this study are encouraged to provide a better understanding of neuronal damage, neuroinflammatory processes and brain deficits of regions of interest in MAP and SCZ.